Evaluation of the antioxidant properties of ginseng green nanoparticles in protecting male rats against potassium dichromate toxicity - Hamza, Mohammed A.; Hassan, Mayada S.; Mousa, Rana F.; Majed, Marwa S. (Journal of Kerbala for Agricultural Sciences, 2024)
Potassium dichromate is a powerful oxidizing agent that is used in numerous industrial and laboratory procedures. It is known to cause cancer, but it can also exacerbate respiratory problems, burn skin, and even induce lung cancer. A popular herbal supplement, ginseng also has multiple medical applications. It could have anti-inflammatory and antioxidant properties in addition to increasing energy and cognitive performance and decreasing stress. to examine whether male rats may be protected from the harmful effects of potassium dichromate by using ginseng nanoparticles. Seven distinct animal species were included in the study. Every one of the 42 rates makes use of 6 male rats. The rats exposed to potassium dichromate had significantly higher levels of malondialdehyde (MDA) and lower levels of catalase and superoxide dismutase (SOD) compared to the other groups in the study, indicating that it had a deleterious impact on their health. The present results showed Ginseng green NPs enhance all of the above listed measures.